2015
DOI: 10.1002/ps.4170
|View full text |Cite
|
Sign up to set email alerts
|

Propesticides and their use as agrochemicals

Abstract: The synthesis of propesticides is an important concept in design of modern agrochemicals with optimal efficacy, environmental safety, user friendliness and economic variability. Based on increasing knowledge of the biochemistry and genetics of major pest insects, weeds and agricultural pathogens, the search for selectivity has become an ever more important part of pesticide development and can be achieved by appropriate structural modifications of the active ingredient. Propesticides affect the absorption, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 82 publications
0
135
0
5
Order By: Relevance
“…The vectorization of an agrochemical compound consists of modulating and controlling the distribution of an active ingredient within the plant by associating it with a vector. In the case of molecular vectorization, which is discussed in this review, the vector group will be introduced into a biologically active compound and the resulting molecule will be a propesticide . Once the molecule reaches the target, it will release the parent molecule by the action of various enzymes or by a chemical hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The vectorization of an agrochemical compound consists of modulating and controlling the distribution of an active ingredient within the plant by associating it with a vector. In the case of molecular vectorization, which is discussed in this review, the vector group will be introduced into a biologically active compound and the resulting molecule will be a propesticide . Once the molecule reaches the target, it will release the parent molecule by the action of various enzymes or by a chemical hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Upon entering the leaf, the carbonic ester group of spirotetramat (log P = 2.5; p K a = 10.7) is hydrolyzed in the plant to form the insecticidally active enol metabolite. This metabolite (log P = 0.3; p K a = 5.2) is one of the very few phloem mobile insecticides used against sap‐feeding pests …”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The apparent preference for interaction at the high affinity site is comparable to that of SFX and it has been suggested that cis-neonicotinoids are useful compounds to discriminate between the two IMI binding sites. 132) However these compounds are the Michael adducts of crotonaldehydes with nitromethyleneimidazole (NMI), [133][134][135] a compound known since the early 1990's 66,136,137) and the authors have not ruled out the possible release of NMI in the aqueous experimental conditions. Indeed, unlike IMI, saturation studies using [ 3 H]-NMI detected only the presence of a single binding site.…”
Section: Sulfoximinesmentioning
confidence: 99%